PENGEMBALIAN KERUGIAN KEUANGAN NEGARA MELALUI PENDEKATAN KEADILAN RESTORATIF DALAM PERKARA TINDAK PIDANA KORUPSI DANA DESA DI KABUPATEN HALMAHERA BARAT - Hama, Albert; Mau, Hedwig A.; Ismed, Mohammad (SINERGI : Jurnal Riset Ilmiah, 2025)
In Indonesia, corruption in the management of village funds has emerged as a critical concern, particularly because these funds serve as the primary source of financing for village‑level development. This study aims to analyze the regulatory framework governing the restitution of state financial losses in cases of village‑fund corruption and to examine the application of a restorative‑justice approach to recovering such losses in West Halmahera Regency. The theoretical foundation comprises law‑enforcement theory and restorative‑justice theory. This research is classified as empirical legal research, employing a socio‑legal approach. Primary data constitute the principal information source, supplemented by secondary and tertiary materials to enrich the analysis. Data were collected through interviews and document review. A doctrinal (juridical) analysis was conducted to explicate the legal phenomena under investigation. The findings reveal that Indonesia’s anti‑corruption efforts have evolved from a generalized legal framework toward the strengthening of specialized norms and procedures. This progression is embodied in Law No. 31 of 1999, as amended by Law No. 20 of 2001—which refines definitions and increases sanctions; the establishment of the Corruption Eradication Commission under Law No. 30 of 2002; and the establishment of a specialized corruption court pursuant to Law No. 46 of 2009. These instruments integrate preventive mechanisms (such as asset declarations and forensic audits) with repressive measures (including asset seizure, forfeiture, and penal mediation) to both punish offenders and restore state financial losses. Moreover, in the village context—specifically in West Halmahera Regency—a restorative‑justice model that combines mediation, asset restitution, and the engagement of customary community leaders, and that is tailored to local geographic, cultural, and institutional characteristics, has the potential to expedite the recovery of village funds, cultivate a culture of accountability and transparency, and reinforce inclusive, responsive, and sustainable village governance as a foundation for long‑term corruption prevention and enhanced public trust